Patients' Perceptions and Expectations of Family Participation in the Informed Consent Process of Elective Surgery in Taiwan - Mei-Ling Lin, RN, MSN; Wai-Ming Kan, PhD; Ching-Huey Chen, RN, PhD (Elsevier, 2012)
Purpose: This study investigated patients' perceptions and expectations of their families' participation in the informed consent process of elective surgery. Methods: This is a survey study. Anonymous questionnaires that were mailed to potential participants included a demographic data sheet and a scale, measuring patients' perceptions of themselves and their families' participation level in the informed consent process. A convenience sample of patients who had undergone surgery and had been discharged within 4 months from a medical center in southern Taiwan (n = 1,737) were recruited. Results: One hundred and forty-five recipients replied, gaining a response rate of 10.0%, and 120 provided complete data. The mean age of the participants was 56.0 years (range 20-85, SD = 14.98), and more than half were female (54.2%). Twenty-one participants (17.5%) perceived having less family participation than their own participation in the surgery informed consent process, and 40% expected more family participation in the process. The mean scores of the self-rated participation level was significantly higher than that of the families (p < .001). Patients' expectations of family participation were significantly higher than their perceptions of family participation (p < .001). Eleven patients (9.2%) reported having more family participation than they expected. Participants received the most information about the disease during the informed consent process and the least information about alternatives to surgery. Age, gender, number of previous surgeries and admissions influenced the study participants' perceived level of participation in the informed consent process. Conclusion: This preliminary study demonstrates that patients' perceptions and expectations for family participation in the surgical informed consent process vary. Healthcare providers should be aware of patients' expectation to appropriately invite their family into the informed consent process.